2022
DOI: 10.21276/apjhs.2022.9.3.14
|View full text |Cite
|
Sign up to set email alerts
|

Awareness, Perception, and Practice of Obese Patients toward COVID-19: A Study from Tertiary Care Center, India

Abstract: Introduction: COVID-19 has emerged as a global health crisis. It has been established that people with obesity are prone to develop severe manifestations of COVID-19. Since there is no established treatment of the disease, yet, it is essential to increase public awareness toward prevention of infection. This study was aimed to assess the awareness, perception, and practices of obese subjects toward COVID-19 infection. Methods: This cross-sectional study was conducted among 260 obese patients between August 202… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Following this phase, a comprehensive review of the full-text articles was conducted, excluding 186 studies from further consideration. A total of 23 studies, including 21 studies for knowledge, 10,12,13,15,[17][18][19][20][21][22][23][26][27][28][29][30][31][32][33][34][35] 12 studies for attitudes, 10,12,14,15,[19][20][21]23,29,30,34,35 and 12 studies for practice 10,12,[18][19][20][21]23,[29][30][31]35 were included in the meta-analysis (Figure 1).…”
Section: Eligibility Studies and Search Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Following this phase, a comprehensive review of the full-text articles was conducted, excluding 186 studies from further consideration. A total of 23 studies, including 21 studies for knowledge, 10,12,13,15,[17][18][19][20][21][22][23][26][27][28][29][30][31][32][33][34][35] 12 studies for attitudes, 10,12,14,15,[19][20][21]23,29,30,34,35 and 12 studies for practice 10,12,[18][19][20][21]23,[29][30][31]35 were included in the meta-analysis (Figure 1).…”
Section: Eligibility Studies and Search Resultsmentioning
confidence: 99%
“…The most knowledge is related to an African country (Rwanda 97%), 15 and the least is associated with a European country (Romania 10.8%) 26 . Among Asian countries, two studies in India showed very low values for good knowledge 17,29 . Given that knowledge levels might differ significantly across countries and continents; it is possible that a COVID‐19 education program that is designed to accommodate all students won't be successful.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations